Nesting Site Nesting Site Characteristics and Egg Hatching Success of Maleo (Macrocephalon maleo) in Hungayono Sanctuary, Gorontalo: Characteristics of Maleo spawning locations and successful hatching of maleo eggs in Hungayono - Fira Rizka Karim; Burhanuddin Mas’yud; Jarwadi B Hernowo (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2022)
Maleo population is decreasing due to the decline in suitable breeding site. The establishment of a maleo sanctuary in Hungayono aims to increase maleo population by protecting its eggs and increasing the success rate of eggs hatched. This study aims to analyze the characteristics of maleo nesting habitats, to describe the semi-natural maleo egg hatching management in the sanctuary, and analyze the success rate of maleo egg hatching in Hungayono. The results showed that the Maleo nesting sites are clean of bushes and shrubs, but there was still shades from trees or bamboo. The nesting sites are close to rivers and geothermal sources with mixed soil structure. The natural egg burrows has an average depth of 92.8 cm, width of 82.7 cm, temperature of 32.5 oC, and humidity of 90%. Hungayono has seven hatcheries that utilized geothermal heat to hatch Maleo egg semi-naturally. The burrows size in the hatcheries were made according to the size of Maleo eggs, with an average depth of 32 cm and width of 10 cm, the average temperature is 32.5 oC and humidity is 90.8%. The incubation period for the semi-natural hatcheries is 60-80 days. Maleo egg hatching success rate reached 60.18% in which is medium category.